2011 IEEE 52nd Annual Symposium on Foundations of Computer Science 2011
DOI: 10.1109/focs.2011.51
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Explicit Coding for Interactive Communication

Abstract: Abstract-We revisit the problem of reliable interactive communication over a noisy channel, and obtain the first fully explicit (randomized) efficient constant-rate emulation procedure for reliable interactive communication. Our protocol works for any discrete memoryless noisy channel with constant capacity, and fails with exponentially small probability in the total length of the protocol.Following a work by Schulman [Schulman 1993] our simulation uses a tree-code, yet as opposed to the non-constructive absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 16 publications
0
50
0
Order By: Relevance
“…The problem of designing error resilient interactive communication protocols (as opposed to messages) was first studied by Schulman [Sch93], with extensions by [BR11,Bra12,GMS11]. However, in the current paper, we do not require the more complicated ideas of these works, because it turns out that we can obtain our results using simpler protocols that are enough for the error model we consider.…”
Section: Techniquesmentioning
confidence: 75%
“…The problem of designing error resilient interactive communication protocols (as opposed to messages) was first studied by Schulman [Sch93], with extensions by [BR11,Bra12,GMS11]. However, in the current paper, we do not require the more complicated ideas of these works, because it turns out that we can obtain our results using simpler protocols that are enough for the error model we consider.…”
Section: Techniquesmentioning
confidence: 75%
“…We also show that for higher noise rates, no constant-rate interactive protocol exists for tasks that depend on inputs of both parties. Similarly to previous results for interactive communication with adversarial noise [24,5,9], our decoding scheme is inefficient. Very recently, Brakerski and Kalai [2] showed how to augment previous results of interactive communication protocols and achieved efficient schemes that withstand adversarial noise (the computation efficiency was further improved by Brakerski and Naor [3] to O (N log N )).…”
Section: Our Resultsmentioning
confidence: 78%
“…gives a sub-exponential (in N ) construction of a tree code, and Gelles, Moitra and Sahai [9] provide an efficient construction of a randomized relaxation of a tree code of depth N , namely a potent tree code, which is powerful enough as a substitute for a tree code in most applications.…”
Section: For Any Two Paths (Strings) X Y ∈ [D]mentioning
confidence: 99%
“…Followup works by Braverman and Rao [BR11] and by Braverman [Bra12] showed how to improve the error rate to 1/8 (1/4 for non-binary alphabet) and how to improve the computational complexity to 2 Θ(N ) , respectively. Gelles, Moitra and Sahai [GMS11] showed that the computational complexity can be improved to poly(N ) if the channel errors are uniformly distributed (i.e. each bit is flipped with the same fixed probability), however their simulator still required exponential time for adversarial channels.…”
Section: Introductionmentioning
confidence: 99%